The utility of 99mTc-Pyrophosphate SPECT in diagnosisof latent myocarditis in patients with atrial fibrillation - Sazonova S. I. Svetlana Ivanovna; Iljyushenkova Yu. N. Yuliya Nikolaevna; Batalov R. E. Roman Efimovich; Rogovskaya Yu. V. Yuliya Viktorovna; Lishmanov Yu. B. Yury Borisovich (2015, 2015)
Title screen